PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Widarti Widarti (KOLEGIAL, 2013)
This research was conducted to examine the effect of partially or simultaneously comprising Financial Ratios Current Ratio, Debt to Equity Ratio, Return on Assets, Return on Equity, Earnig Per Share, Price Book Value and Price Earning Ratio affect On Manufacturing Companies Stock Price Indonesia Stock Exchange listed securities. Sampling technique is done by using a purposive sampling method. And acquired 30 companies as the study sample. Observation period is for 3 years 2009 to 2011. The data analysis technique used is multiple linear regression analysis. Simultaneous analysis of the results of the Current Ratio, Debt to Equity Ratio, Return on Assets, Return on Equity, Earnig Per Share, Price Book Value and Price Earning Ratio significant effect on stock prices with a significant level of 0.000. But partially Debt to Equity Ratio, Earnig Per Share, Price Earning Ratio significant effect on stock prices with a significant level of Debt to Equity Ratio is at 0,029, Earnig Per Shareis at 0,000, Price Earning Ratio of 0.003. While the Current Ratio, Return on Assets, Return on Equity, Book Value Price does not significantly affect the stock price.